Flexibility of interconnected power system operation: Analysis, evaluation and prospection. Issue 3 (27th October 2020) - Lin, Wei; Yang, Zhifang; Yu, Juan
Abstract: Cross‐region power exchange plays a significant role in the efficient utilization of power resources. An increased power demand and renewable integration leads to a decreased security margin of power system operation. The operational flexibility in an interconnected power system can be further extended by expanding the operating region of each power system. In this study, the potential flexibility in an interconnected power system is summarized from cross‐region and intra‐region perspectives. A unified approach is presented to evaluate the flexibility by multi‐parametric programming. An illustrative example and a 661‐bus utility system are utilized to validate the proposed unified approach. A non‐iterative framework that considers the flexibility in the interconnected power system operation is presented. Relevant lines of future research have also been indicated for practical implementations of the flexibility.